(untitled) (Mongolian Journal of Geography and Geoecology, 2025)
River water quality is crucial as rivers support multiple uses in human needs as well as in sustaining the aquatic ecosystems. In this study, we assessed the physicochemical characteristics and water quality of the Delgermurun River Basin (DRB). We collected water samples from 16 sites along the Delgermurun River and its tributaries in June 2024. Eleven physicochemical parameters were measured onsite, and a permanganate index (CODMn) was analyzed in the laboratory. Seven heavy metals (Mn, Zn, Co, Ni, Mo, As, and Cd) were analyzed at SGS IMME Mongolia LLC, a certified laboratory. Principal component analysis (PCA) was used to explore variations in physicochemical characteristics, while water quality index (WQI) and heavy metal pollution index (HPI) were calculated to assess overall water quality of the DRB. According to the PCA, pH, turbidity, water temperature (Temp.), total dissolved solids (TDS), and elevation contributed the most to variation across the DRB. The highest values of pH, turbidity, and Temp. were found at lower sites (DELBugsei, DELG03, and DELW01), while the highest TDS was recorded at DELR02. In terms of the water quality, WQI and HPI values ranged from 0.04 to 0.1 and 5.98 to 29.20, respectively, remaining within the category of “very clean” by WQI and level of lower pollution by HPI (MNS 4586:1998). Our findings indicate that physicochemical parameters and water quality varied across the DRB, but it remains suitable for potable use. Our results can inform future water resource management, for example, identifying and protecting critical habitats, such as those for the endangered taimen (Hucho taimen), and contributing to the conservation of the DRB ecosystem.